Evaluating the Effectiveness of an Evidence-Based Practice in Neonatal Resuscitation among Birth Asphyxiated Newborns in a Developing Country - Lydia Boampong Owusu; Joseph Shahadu Issifu; Emmanuel Odame Owiredu; Sandra Addai-Henne; Stella Kofie Aniewu; Joyce Boatemaa Manu; Perpetual Ntiamoah; Catherine Kroamah Dwumfour; Abigael Emikpe; Abdul-Fatawu Suglo Zakaria (SAGE Open Nursing)
Introduction The World Health Organization emphasizes that neonatal resuscitation performed in the first “golden minute” following birth can influence both immediate and long-term outcomes of newborns, especially asphyxiated ones. The modes of resuscitation, which is an evidenced-based practice, require evaluation to identify their effectiveness. Objectives This study evaluated neonatal resuscitation techniques and their effectiveness in the management of asphyxiated neonates during the perinatal period. Design Cross-sectional design with observation of delivery and immediate care of 254 newborns in five hospitals from April to June 2022. Methods Neonatal resuscitation and demographic characteristics were noted. Data were analyzed descriptively using STATA 17 and Cramer’s V test of association between APGAR scores and resuscitation modes was done with statistical significance established at p  ≤ .05. Results Neonatal resuscitation was primarily performed by midwives (98.4%), with 48.8% of the infants resuscitated after birth. The most common modalities of resuscitation were drying, keeping warm, rubbing the back, and flicking the feet, with 46.0% started on bag and mask ventilation. The success rate of resuscitation was impressive (58.1%), satisfactory (38.7%), and poor (3.2%). There was a strong association of the first minute APGAR score with drying the neonate ( p = .0001, φc = 0.619), keeping the neonate warm, and rubbing the back of the neonate ( p = .0001, φc = 0.613). However, their association with the fifth minute APGAR score was weak ( p = .002, φc = 0.222). Feet flicking has no significant association with the fifth minute APGAR score. Conclusion Neonatal resuscitation, which is an evidence-based practice, is more effective in the first minute than in the fifth minute. Regular training of midwives to update their resuscitation skills is important to promote timely and efficient resuscitation of newborns. Further studies into the advancements in resuscitation modes and the use of technology to improve resuscitation beyond the first minute are recommended.